Effect of non-identity of beam position monitors manufacturing on measurement accuracy of the reference orbit coordinates - Ivashchenko, V.E.; Karnaukhov, I.M.; Trotsenko, V.I.; Shcherbakov, A.A. (Вопросы атомной науки и техники, 2007)
Effect of geometrical and electrical non-identity of monitors manufacturing on accuracy of measurement of beam position has been studied. It has been shown, that even providing mechanical accuracy of monitor manufacturing of about ±100µm and deviation of electric capacity of electrodes equal to ±2%, their operating characteristics near the monitor center may differ from each other more than on ±300µm. Вивчено вплив геометричної та електричної неідентичності виготовлення датчиків на точність вимірювання положення пучка. Показано, що навіть при забезпеченні механічної точності виготовлення датчиків ±100 мкм та розкиду електричної ємкості електродів ±2% їх робочі характеристики поблизу центру можуть відрізнятись один від одного більше ніж на ±300 мкм. Изучено влияние геометрической и электрической неидентичности изготовления датчиков на точность измерения положения пучка. Показано, что даже при обеспечении механической точности изготовления датчиков ±100 мкм и разброса электрической емкости электродов ±2% их рабочие характеристики вблизи центра могут отличаться друг от друга более чем на ±300 мкм.